Stent thrombosis after primary percutaneous coronary intervention in comatose survivors of out-of-hospital cardiac arrest: Are the new P2Y12 inhibitors really more effective than clopidogrel?. (January 2016) - Gouffran, Guillaume; Rosencher, Julien; Bougouin, Wulfran; Jakamy, Reda; Joffre, Jérémie; Lamhaut, Lionel; Dumas, Florence; Cariou, Alain; Varenne, Olivier
Abstract: Aim: High rates of stent thrombosis (ST) have been reported in patients with out-of-hospital cardiac arrest (OHCA) who require a primary percutaneous coronary intervention (PCI). The aim of this study was to assess risk factors of ST in this population with a special focus on antiplatelet therapy administered during the acute phase. Materials and methods: We conducted a retrospective observational study in patients treated with primary PCI after OHCA between 2011 and 2013 in our center. All consecutive patients were treated with mild therapeutic hypothermia and dual antiplatelet therapy after primary angioplasty. Results: A total of 101 consecutive patients were included in the present analysis. Mean age was 61.3 ± 12.7 years and 75% of patients had an initial ventricular fibrillation. All patients received aspirin before PCI. P2Y12 inhibitors were administered after PCI and included clopidogrel (47.5%), prasugrel (21.8%) or ticagrelor (29.7%). The survival rate at discharge was 44.5%. We identified 11 cases (10.9%) of definite or probable ST (clopidogrel ( n = 2), prasugrel ( n = 4) and ticagrelor ( n = 5)) occurring at a median of 2 days after PCI. No specific predictors were found to be significantly associated with ST. New P2Y12 inhibitors were associated with more ST compared to clopidogrel (17.3% vs. 4.2%; respectively, p = 0.05). ST was associated with a decreased left ventricular ejection fraction ( p = 0.007) and with a trend toward a higher mortality compared to patients without ST (82% vs. 52%, p = 0.06). Conclusion: The incidence of ST in OHCA survivors is high and associated with poor clinical outcome. The use of new oral P2Y12 inhibitors does not appear to be associated with a reduction in ST compared to clopidogrel.